Impact of Physician–Patient Language Concordance on Patient Outcomes and Adherence to Clinical Chest Pain Recommendations. (12th March 2020) - Altman, Danielle E.; Sun, Benjamin C.; Lin, Bryan; Baecker, Aileen; Samuels‐Kalow, Margaret; Park, Stacy; Shen, Ernest; Wu, Yi‐Lin; Sharp, Adam
ABSTRACT: Objectives: The objective was to evaluate if there is an association between patient–physician language concordance and adverse patient outcomes or physician adherence to clinical recommendations for emergency department (ED) patients with chest pain. Methods: We conducted a retrospective observational study of adult ED chest pain encounters with a troponin order from May 2016 to September 2017 across 15 community EDs. Outcomes were 30‐day acute myocardial infarction or all‐cause mortality, hospital admission/observation, or noninvasive cardiac testing. To assess patient outcomes, we used the overall cohort. To assess adherence to clinical recommendations, we used a subgroup of patients with a low‐risk HEART score. A mixed‐effects logistic regression model was used to compare the odds of the outcomes between language concordant and discordant patient–physician pairs, controlling for patient characteristics. Results: Overall, 52, 014 ED encounters were included (10, 791 low‐risk HEART encounters). Of those 6, 452 (12.4%) encounters were language discordant and 1.7% in each group had an adverse outcome. Adjusted models demonstrated no increased risk for language discordant ED encounters when comparing adverse outcomes (odds ratio [OR] = 0.96, 95% confidence interval [CI] = 0.6 to 1.5) for all patients or recommended care (OR = 1.02, 95% CI = 0.87 to 1.2) for low‐risk patients. Conclusions: No associations were found between patient–physician language concordance and outcomes or physician adherence to clinical recommendations for ED patients with chest pain. Accessible and effective interpretation services, combined with a decision support tool with standard clinical recommendations, may have contributed to equitable care.